A Calendar of Days: The Pécs International Folk Days - Rouse, Andrew (Ethnologies, 2001)
The first Pécs International Folkest took place in 1986 and was funded by the various state agencies existing in the years of socialism. Today the festival still continues, although like all festivals it has gone through some tricky patches over the years. This article examines, through newspaper cuttings, archive materials and the inaccurate memories of the many organisers, how it has survived the transfer from one state-dominated regime to another based on a new capitalism that has pushed cultural events, always an important part of the socialist political voice, into the background.